Understanding historic concrete - Collie, Michael; Bussell, Michael; NBS Learning Channels; Insight Media (Firm). (New York Distributed by Insight Media, 2010)
Concrete is used more than any other man-made material and the UK has a vast number of concrete structures of varying ages. For the engineer tasked with appraising, repairing or altering a concrete structure, concrete's opacity presents problems with assessing the structure. For example, is the concrete in question mass concrete or reinforced, or even pre-stressed? Perhaps it is not structural at all, merely disguising a steel frame? It is always important to understand what materials you are dealing with. This programme aims to give the engineer a feel for what is likely to be found at different dates and with different types of structures. It is in the form of an interview with Michael Bussell.
Presenter, Michael Collie.
DVD.
Keywords: Concrete; Concrete construction; Video discs